Comparison of integer and fractional order robust controllers for DC/DC converter feeding constant power load in a DC microgrid. (December 2017) - NasimUllah,; Asghar, Muhammad; Khattak, Abraiz; Rafiq, Muhammad Mohsin
Abstract: DC/DC converter's when feeding the constant power loads (CPLs) are sensitive to the instabilities due to the induced negative impedance characteristics. An efficient control system is crucial to overcome the de-stabilization problem for the DC/DC converters. This article proposes an integer and fractional order terminal sliding mode (TSMC) controllers for DC/DC boost converter feeding the constant power load (CPL) in a typical DC microgrid configuration. Novel integer and fractional order nonlinear sliding manifolds are proposed and based on the Lyapunov theorem terminal sliding mode controllers (TSMC) are formulated and its stability is guaranteed. Finally, numerical simulations are presented to compare the performance of the integer TSMC, fractional TSMC and classical SMC.